Analysis of the Kinematics and Workspace of a Tripod Parallel Robot - Sun Shuai; Song Gongfei; Huang Xiancun (Jixie chuandong)
By analyzing the structure of Tripod parallel robot,a single branch chain analysis model is established. The kinematics analysis of robot is carried out by means of geometric analysis,and the expression of inverse kinematics is obtained. On the basis of the inverse solution analysis,the forward kinematics analysis formula is solved,and by using the numerical method of Newton iteration,the forward kinematics position is calculated. Combined with specific examples,the feasibility of kinematics analysis is verified by using MATLAB software programming. In order to further study the performance of the robot,according to the inverse kinematics of the robot,the workspace of the robot is analyzed. According to the Jacobi matrix of the robot,three kinds of singular configurations of the mechanism are discussed. Finally,the workspace map is drawn by MATLAB software program with the size parameters of the mechanism.